Penciri Sifat Agronomik Kedelai yang Dapat Beradaptasi di Lahan Basah - , Nurlianti; Wahju Qamara Mugnisjah; Muhammad Hasjim Bintoro Djoefrie Hasjim Bintoro Djoefrie; Endang Sjamsudin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
Arable land-use conversion into activities of non-agricultural production may encourage the use of wet region for soybean production. In this respect, a research on the adaptability of 25 soybean varieties to saturated soil has been conducted in the field. A randomized complete block design with 3 replicates was used in this experiment. Results of the experiment showed the adaptability differences among the 25 soybean varieties tested. Based on their yield, soybean adaptability to saturated soil condition was not related to plant growth type, but could be influenced by plant age. With an exception for Tidar (a high yielding variety belonging to the intermediate age), the late varieties produced highe  yield than that of the intermediate ones. It was concluded that the varieties belonging to high yielding ones were  characterized by the existence of positive correlation of pod number with nodule number and relative growth rate and of nodule number with relative growth rate and leaves area index. Key words: Soybean, Adaptation, Saturated soil, Agronomic traits